An exploratory study on rabies exposure through contact tracing in a rural area near Bengaluru, Karnataka, India. - N R Ramesh Masthi; Pruthvi S (Public Library of Science (PLoS), 2018)
NEED FOR STUDY:Rabies is a neglected zoonotic disease. Given the low incidence, apart from the existing reporting syst, there is a need to look for other means of case detection strategies for rabies. Contact tracing is one such method to efficiently capture information. OBJECTIVES:To find out the rabid status of biting animal through contact tracing and to determine health seeking behavior of the bite victims. MATERIALS AND METHODS:An exploratory study using contact tracing was conducted during the first quarter of 2017 in villages coming under three Public Health Centers. The households of the bite victims were visited and details of rabies exposure obtained from the bite victim/ adult responsible respondent using a standardized questionnaire. RESULTS:A total of 69 dog/cat bite cases were identified. 69.5% of bites were by stray dogs. 97.1% bite victims had Category III bites. Only 4.5% bite victims had taken PEP. 70.1% of animal bite cases were administered ARV. Only 7.2% bite victims had exposure to probable rabid animals. All dog bite victims were alive after 3 months of follow up. CONCLUSION:Contact tracing was successful in case detection of probable rabid animal exposures and suitable for a period of one year.